History and climate change : a Eurocentric perspective - Brown, Neville (Routledge studies in physical geography and environment ;, 2001)
This book is a balanced and comprehensive overview of the links between climate and man's advance from pre-history to modern times. It is a synthesis of the many historical and scientific theories regarding man's progress through the ages.